Do Female Western Mosquitofish, Gambusia affinis, Prefer Ornaments That Males Lack?. (27th May 2016) - Casner, Ariel M.; Fackelman, Heather C.; Degtyareva, Olga; Kight, Scott L.
Abstract: Some species in the family Poeciliidae are known for extravagant male ornaments and courtship behavior (e.g., guppies), but the majority of poeciliids are characterized by coercive male copulation attempts that seem to circumvent female choice. In some lineages with male ornaments, female sensory bias may have preceded the evolution of corresponding male signals. We examined female preferences for colorful ornaments in Western mosquitofish, Gambusia affinis, in which males lack ornamentation and reproduce primarily through coercive mating attempts. We found that females exhibited a positional affinity for males that were artificially ornamented with blue coloration over males that had been treated with a transparent ornament. Females exhibited the opposite effect for males treated with red ornaments. In contrast, focal females did not exhibit behavioral discrimination between two live stimulus females or two models (silver fishing lures) with blue vs. transparent ornaments. This suggests a sexual context for female discrimination between males based on ornament color and whether an ornament was present. Because tribe Gambusiini is the basal branch of family Poeciliidae, the results of this study are consistent with the hypothesis that female responsiveness to male coloration is the ancestral poeciliid character state.